Permafrost - Legget, R. F. (1972)
The upsurge of public interest in northern regions in recent years has brought the name `permafrost' into the market place. The proposed construction of pipelines for gas and oil from the Arctic Coast to southern Canada is now generally known to be complicated by the existence of permafrost along considerable parts of the routes that may be followed. The expenditure of over $20,000,000 by groups of oil, gas and pipeline companies on test installations and other research work in the North, all in connection with the problem of building on permafrost, shows clearly the economic significance of this unusual northern problem. Le regain d'intérêt qu'a manifesté le public pour les ré gions du Nord au cours des dernières années a rendu familier le terme "pergélisol". Les projets de construction de gazoducs et d'oléoducs depuis la Côte de l'Arctique jusqu'au Sud du Canada se heurtent à l'existence de pergélisol dans une partie considérable des régions que traverseraient ces pipelines. Des groupes de sociétés de pétrole, de gaz et de pipe-lines ont dépensé plus de vingt millions de dollars pour les installations d'essais et autres travaux de recherches dans le Nord concernant les problèmes que soulè vent les travaux de construction dans le pergélisol. C'est là une indication de l'importance économique de ce problème particulier. Peer reviewed: No NRC publication: Yes